2010
DOI: 10.1002/ajmg.a.33345
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary multiple exostoses with spine involvement in a 4‐year‐old boy

Abstract: Hereditary multiple exostosis (HME) is an autosomal dominant disorder characterized by multiple osteochondromas. We describe a case of acute cervical spinal cord compression arising from an exostosis at the lamina of C7 and T1 in a 4-year-old Mexican-American boy with HME. His affected sibling also displayed spinal cord compression because of a bony exostosis. Acute cervical spinal cord compression resulting from osteochondroma is a serious complication of HME. (c) 2010 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Some cases of patient showed significant growth in adulthood, the incidence of about 25%. 6,7) It's generally agreed that when there are no symptoms present, a HME patient could either avoid any treatment or postpone operation until adolescence. However in this child the large costal cartilage exostosis intruded into the pleural cavity and leads to chest pain and chest distress, so a minimally invasive VATS was given.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of patient showed significant growth in adulthood, the incidence of about 25%. 6,7) It's generally agreed that when there are no symptoms present, a HME patient could either avoid any treatment or postpone operation until adolescence. However in this child the large costal cartilage exostosis intruded into the pleural cavity and leads to chest pain and chest distress, so a minimally invasive VATS was given.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed 11 patients younger than 10 years of age with evidence of cord compression atributable to osteochondromas (Table 1) [1‐10]. Of these, 2 cases were the result of solitary lesions and the other 9 were associated with HMO.…”
Section: Discussionmentioning
confidence: 99%
“…The condition, also known as diaphyseal aclasia, hereditary multiple exostosis, and hereditary multiple enchondromatosis, is characterized by multiple cartilage‐capped bony outgrowths. The disease usually involves the long bones, scapulae, pelvic bones, and, rarely, the axial skeleton [2‐7]. In previous reports, authors have described how HMO can also affect the spine, most commonly the external part of the lamina [1,3,4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Roach et al [11] ont rapporté trois observations pédiatriques dans lesquelles étaient décrits une marche instable, une paralysie de l'impulsion après une chute mineure et le développement au cours de l'évolution d'une myélopathie avec quadriplégie. Récemment, deux cas cliniques ont été rapportés, l'un concernant un jeune garç on âgé de quatre ans [12] et l'autre une jeune fille âgée de quatorze ans [9], comportant une atteinte médullaire cervicale et une raideur du rachis cervical. Il est nécessaire de rechercher des troubles de la marche avec des chutes, des signes de myélopathie comme une faiblesse des extrémités, des paresthésies, une souffrance radiculaire ou des troubles mictionnels [10,11,13].…”
Section: Discussionunclassified